Ketogenic diet improves disease activity and cardiovascular risk in psoriatic arthritis: A proof of concept study - Roberta Ramonda; Francesca Ometto; Giovanni Striani; Giacomo Cozzi; Daniela Basso; Filippo Evangelista; Mariagrazia Lorenzin; Laura Scagnellato; Ada Aita; Marta Favero; Filippo Brocadello; Andrea Doria (PLoS ONE, 2025)
Objectives Very low-calorie ketogenic diet (VLCKD) is a low-carbohydrate, low-calorie regimen that leads to rapid weight loss and may reduce inflammation. This study assessed the impact of VLCKD on anthropometric measurements, inflammatory biomarkers, metabolic health, and cardiovascular risk in psoriatic arthritis (PsA) patients moderately overweight or in class I obesity. Methods A proof-of-concept single-arm monocentric study involved PsA patients undergoing a 9-week VLCKD treatment. Patients with Body Mass Index (BMI) ≥27 and <35, in stable (≥6 months) remission or low disease activity, as defined by Disease Activity in PSoriatic Arthritis (DAPSA) score, were included and underwent nutritional evaluations every 3 weeks. The study analyzed changes after the VLCKD intervention and the association between changes of anthropometric parameters and clinical and laboratory variables. Results Twenty patients were enrolled since April 2022 and completed the study in May 2023. Median baseline BMI was 30.9 (interquartile range 29.1–33) kg/m². All participants exhibited low baseline disease activity, which correlated with BMI (Spearman’s correlation coefficient (rs)=0.59,p=0.007). Following VLCKD, significant improvements were observed in all anthropometric measures (BMI -3.5[-4;-2.6]), PsA activity (DAPSA -6.1[-16.8;3.7]), cardiovascular parameters (SCORE2 index -0.2[-0.7;0.1]), insulin resistance (Homeostatic Model Assessment-Insuline Resistance -2.1[-1.1;-3.0]), and lipid profile. Most inflammatory biomarkers remained within normal limits. BMI reduction correlated with changes in DAPSA scores (rs=0.52,p=0.020). Patients with higher baseline weight or clinical activity experienced more pronounced improvements. Conclusions VLCKD significantly improved PsA activity and metabolic health. Patients with a higher BMI and less controlled disease are particularly motivated and could benefit more from VLCKD compared to those with lower BMI or better disease control.